Evaluation of the effect of initial solid matter concentration and season on anaerobic biodegradation of municipal solid wastes - Tugba Keskin; Yasemin Ersoy; Nuri Azbar (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The necessity for reduction of fossil fuelconsumption and the increasing energy costs drives the interest in developmentof alternative renewable energies during past years. OFMSW (Organic Fraction ofMunicipal Solid Wastes) is a valuablesource, while it can be converted to biogas via anaerobic digestion. In thisstudy The anaerobic digestibility andmethane generation potential of the organic fraction of municipal solid wastes(OFMSW) sampled during three seasons (autumn, winter and summer) of a year weredetermined using batch bioreactors with varying initial dry solid matter ratios(DM:5-35 %). Batch experimentswere carried out both with and without anaerobic inoculum. On the basis of the laboratory results,biogas production potentials were determined to be in the range of 229 - 484 m3/tonDM forexperiment using anaerobic inoculum and 84 – 176 m3 /ton DM forexperiments without inoculum. The best organic matter combination belongs toautumn season and the best concentration was observed as 20% DM.